The Influence of Family Support and Pesantren Climate on Academic Resilience: The Mediating Role of Self-Esteem at PPTQ Ar-Rahman Tekung, Lumajang - Afifah, Rofael (Risalatuna Journal of Pesantren Studies, 2024)
This article investigates the strategic role of pesantren in shaping students’ character and academic capabilities in Indonesia. The study aims to analyze the influence of family support and pesantren climate on academic resilience, with self-esteem acting as a mediating variable. Employing a quantitative approach, the research utilized descriptive and inferential analysis techniques. Data were collected through questionnaires and analyzed using path regression analysis. The results indicate that family support has a significant direct effect on self-esteem (β = 0.275; p < 0.001), and pesantren climate also has a significant direct effect on self-esteem (β = 0.289; p < 0.001). Furthermore, self-esteem significantly influences academic resilience (β = 0.256; p = 0.003). Both family support (β = 0.233; p = 0.004) and pesantren climate (β = 0.232; p = 0.004) exhibit direct effects on academic resilience. Additionally, indirect effects are identified, where family support (β = 0.070; p = 0.009) and pesantren climate (β = 0.073; p = 0.001) influence academic resilience through self-esteem. The study concludes that family support and pesantren climate are critical predictors of students’ academic resilience, operating both directly and indirectly via the enhancement of self-esteem.